Intergroup Contact and Prejudice Reduction: Prospects and Challenges in Changing Youth Attitudes. Issue 3 (September 2022) - Tropp, Linda R.; White, Fiona; Rucinski, Christina L.; Tredoux, Colin
Intergroup contact has long been lauded as a key intervention to reduce prejudice and improve intergroup attitudes among youth. In this review, we summarize classic perspectives and new developments in the intergroup contact literature, highlighting both prospects and challenges associated with achieving desired youth outcomes through contact. First, we review literature showing how positive intergroup outcomes can be facilitated through cultivating optimal conditions for contact, as well as by attending to youth's emotional responses to contact. We then discuss how desired contact outcomes may be inhibited by limited understanding of ways in which contact strategies may affect youth across developmental stages, as well as by limited focus on societal inequalities and intergroup conflict, which require examination of outcomes beyond prejudice reduction. We also review growing bodies of research on indirect contact strategies—such as extended contact, vicarious contact, and online contact—showing many options that can be used to promote positive relations among youth from diverse backgrounds, beyond the contact literature's traditional focus on face-to-face interaction. We conclude this review by acknowledging how understanding both prospects and challenges associated with implementing contact strategies can enhance our capacity to prepare youth to embrace group differences and build more inclusive societies.